Manado Malay code switching at the Sario sub-district office: Alih Kode Bahasa Melayu Manado di Kantor Camat Sario - Eva Yoan Poluan; Djeinnie Imbang; Maya Warouw (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This study aims to: 1. identify the forms of code switching in Manadonese Malay at the Sario Manado Sub-district Office. 2. To analyze the factors causing code switching in Manadonese Malay at the Sario Sub-district Office. This study uses a qualitative descriptive research method. The results of this study identified that code switching used in conversations between employees, THL and environmental leaders at the Sario Sub-district Office is in 2 (two) forms, namely Internal code switching and External code switching. Factors that influence code switching are the ethnic background of the speaker, the ethnic background of the interlocutor and the official language that has been agreed upon in an official meeting and the multilingual abilities of the speaker and interlocutor.